LDF (less dirty first): dirtiness‐aware cache replacement policy for PCM main memory. Issue 25 (1st December 2013) - Yoo, S.; Lee, E.; Bahn, H.
Abstract : A new last‐level cache replacement policy for systems with a phase‐change memory (PCM) main memory is presented. The proposed policy aims at reducing the write traffic to PCM by considering the fine‐grained dirtiness of cache blocks when making a replacement decision. Experimental results show that the proposed policy reduces the write traffic to the PCM by 26 and 17% on average and up to 52 and 33% compared to not recently used and re‐reference interval prediction, respectively.